Acute injury of hippocampal dentate gyrus and hilus by elevated external potassium - Basile, Cristina (University of Ottawa (Canada), 2006)
Potassium is the most abundant ion species in the mammalian central nervous system. Under normal physiological conditions, most K+ in the brain tissue resides within the cytoplasm of neurons, glia, and axons. However, brain injuries such as trauma or ischemia may cause large amounts of K + to leak out. This sudden increase of K+ in the interstitial space may have severe pathological consequences. Animal models suitable for studying K+-mediated tissue injury are uncommon in the literature. Therefore, the main objectives of this thesis were: (1) to develop an animal model of K+-induced tissue injury and (2) to examine the mechanism and cellular events that are potentially responsible for the observed tissue injury. We chose to study the dentate hilus (DH) of the hippocampus because previous studies have shown that K+ homeostasis in this region is highly sensitive to traumatic brain injury. Approximately 150 adult male rats were used throughout this study. Under anesthesia, a small volume of K+ solution was injected into either the left or right hippocampal hilus. This was followed by an injection of the vehicle solution into the corresponding DH region of the contralateral hippocampus. The animals were then sacrificed at different time points post-K + or drug injections. Tissue sections were collected for immunofluorescent processing and quantification. The main findings are the following: (1) Microinfusion of low concentrations of K+ into the DH produced, within minutes, a large tissue cavity along the subgranular zone (SGZ). The SGZ is mainly composed of the initial segments of mossy fibers from granular cells of the dentate gyrus, interneurons of the hilus and astrocytes. (2) The occurrence of the tissue split was accompanied by rapid injury and destruction of glial cells. There was no detectable death of granular neurons. (3) The K +-induced tissue split can be reliably reproduced by the injection of the Na+,K+-pump inhibitor ouabain, which led to a rapid, endogenous increase of K+ in the extracellular space (ECS). However, injections of equal volume of NaCl, CaCl2 or distilled water did not induce tissue split in the DH. (4) In the presence of K+ channel blockers, both ouabain and exogenously applied K+ were no longer effective in producing the tissue split. Based on the above results, it is concluded that the tissue integrity of hippocampal dentate hilus is extremely vulnerable to high external K +. Glial cell death seems to play an important and early role in the occurrence of K+-induced tissue damage. Since traumatic brain damage as well as temporal lobe epilepsy exhibits similar pathophysiological features to K+-induced tissue injury, we propose that the latter can be used as a useful animal model for future mechanistic and therapeutic investigations.
Keywords: Biology, Molecular.